If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 = 6(y + -6) + 2y Reorder the terms: 20 = 6(-6 + y) + 2y 20 = (-6 * 6 + y * 6) + 2y 20 = (-36 + 6y) + 2y Combine like terms: 6y + 2y = 8y 20 = -36 + 8y Solving 20 = -36 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. 20 + -8y = -36 + 8y + -8y Combine like terms: 8y + -8y = 0 20 + -8y = -36 + 0 20 + -8y = -36 Add '-20' to each side of the equation. 20 + -20 + -8y = -36 + -20 Combine like terms: 20 + -20 = 0 0 + -8y = -36 + -20 -8y = -36 + -20 Combine like terms: -36 + -20 = -56 -8y = -56 Divide each side by '-8'. y = 7 Simplifying y = 7
| 50=r+8 | | 50=r+r-8 | | 50-8=r | | 50-8=2r | | X/23=15/33 | | x-11=17-3x | | X/22 | | -7y-21=0 | | c=18+3c | | 5d=40-5d | | 7d-8=-d+56 | | 4j-3=-2j+45 | | 5y+6=-y+66 | | 36c-27=3(8c+3) | | 2(4c-5)=2c+8 | | 8y=15+3y | | -3=3(u+7)-6u | | 6a-8=a+32 | | 9j-9=3j+39 | | 9j+9=3j+39 | | 4a+5=a+32 | | 2b^2-10b-48=0 | | -32=3(w-4)-7w | | -8w+4=2(w-8) | | (4a-5)+(9-2a)= | | A+7b+3A+5b= | | 6(4r-1)=12 | | (5+4i)(3+2i)=0 | | 2.5x+2=6 | | 2.5+2=6 | | 2p+8=24 | | -3u-4=8(u+5) |